Islamic management: the power of Qur'anic thinking - Fontaine, Rodrigue Ancelot Harvey (Akademi Sinergi Sdn Bhd, 2020)
This textbook was written for students interested in Islamic Management. It contains 15 chapters and revolves around the Prophetic Leadership Model. Each chapter is based on a published article. The book summarizes the data collected from over 3,000 participants between 2010 and 2020.